Delivering strategic land use/transport planning solutions and major projects the importance of spatial planning : delegate information : Tuesday 28 October 2003, Church House Conference Centre, Westminster, London (Thomas Telford, 2003)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in London on 28 October 2003.